Avoiding Greenwashing in the Construction Industry : From the Perspective of Finnish MNCs - Pölkki, Noona (My University, 2024)
The rapidly increasing climate change has led to consumers choosing more sustainable options and governments adding more pressure on companies to be more responsible. The increasing demand has led companies to develop their business strategies in green marketing, to gain a more positive image and, thus, a competitive advantage. Greenwashing activities can have negative impacts and damage the entire brand image. It can lead to weaker brand attitudes, increase serious profit losses, reduced investment, and lead to brand avoidance. Greenwashing can increase consumer scepticism, and in the construction industry, where the ESG challenges are high, greenwashing not only damages MNCs´reputations but also undermines genuine efforts toward sustainable development. Finland has a pioneering role in sustainable development and stricter regulations, which is why this thesis concentrates on the Finnish MNCs. This thesis study how Finnish MNCs in the construction sector can avoid greenwashing. First, by defining what greenwashing is and what the consequences are. Then by examining the key sustainability issues in the construction industry, subsequently, how Finnish MNCs in the construction industry can manage responsibility and accountability. By conducting a literature review, this thesis identifies three key methods to reduce the risk of greenwashing. The three key methods for reducing the risks of greenwashing and promoting sustainable development include third-party verifications and certifications that increase the company's credibility. Secondly, enhancing transparency in corporate responsibility activities. Lastly engaging stakeholders in the sustainability dialogue, which enhances the brand's reputation. Through these methods, companies can reduce the risk of greenwashing and create a more sustainable business.

Nopeasti kiihtyvä ilmastonmuutos on saanut kuluttajat valitsemaan vastuullisempia vaihtoehtoja, sekä valtiota vaatimaan yrityksiltä enemmän raportointia vastuullisuudestaan. Tämän myötä yritykset ovat alkaneet kehittämään liiketoimintastrategioitaan enemmän vastuulliseksi ja saavuttamaan myönteisemmän yrityskuvan ja mahdollisesti tällä tavoin kilpailuetua. Kuitenkin osalla yrityksillä tämä on johtanut ilmiöön nimeltä viherpesu, jolla voi olla negatiivisia vaikutuksia koko yrityskuvaan, aiheuttaa liiketoiminnallisia tappiota, vähentää sijoittajien investointeja ja jopa johtaa koko yrityksen välttämiseen. Viherpesu voi lisätä kuluttajien skeptisyyttä, sekä rakennusteollisuudessa, jossa vastuullisuuteen liittyvät aiheet ovat haastavia, viherpesu ei ainoastaan vahingoita monikansallisten yritysten mainetta, vaan myös heikentää aitoja pyrkimyksiä kohti kestävää kehitystä. Suomella on edelläkävijän rooli kestävässä kehityksessä ja useita maita tiukempi sääntely, jonka vuoksi tämä kanditutkielma keskittyy suomalaisiin monikansallisiin yrityksiin. Kanditutkielmassa selvitetään, miten suomalaiset rakennusalan monikansalliset yritykset voivat välttää viherpesua. Alussa määritellään, mitä viherpesu on, sekä sen seuraukset. Tämän jälkeen tarkastellaan rakennusalan keskeisiä kestävyyskysymyksiä ja myöhemmin, miten suomalaiset rakennusalan monikansalliset yritykset voisivat olla vastuullisempia, sekä miten vastuullisuudesta tulisi viestiä. Kirjallisuuskatsauksen avulla kanditutkielma tunnistaa kolme keskeistä tapaa vähentää viherpesua. Nämä kolme tapaa ovat; kolmannen osapuolen suorittamat tarkistukset tai sertifioinnit; läpinäkyvyyden lisääminen yrityksen toiminnassa; ja sidosryhmien sitouttaminen kestävän kehityksen vuoropuheluun. Näillä menetelmillä yritykset voivat vähentää viherpesun riskiä ja luoda vastuullisempaa liiketoimintaa.
Keywords: Greenwashing, Sustainability, Corporate Social Responsibility, Construction industry, viherpesu, vastuullisuus, yritysvastuu, rakennusala